Mechanical Response of Listric Faults in the Three Gorges Reservoir Area Based on Three-Dimensional Morphological Characteristics - Duan, Guoyong; Wang, Lehua; Deng, Huafeng; Zhang, Jingyu; Luo, Zuosen; Jiang, Qiao (Frontiers in Physics, 2021)
Faults or joints widely exist in rock masses, which deeply affect the mechanical properties of rock. The seismic frequency of the Gaoqiao fault and its surrounding areas in the Three Gorges Reservoir area before and after water storage is significantly higher than that in other areas. In this paper, a curved joint is used to simulate the occurrence characteristics of the Gaoqiao fault, and the influence of reservoir water is simulated by adjusting the fracture water pressure. Compared with the changes of joint surface morphology parameters before and after the test, it is found that the macro failure characteristics of rock samples are in good agreement with the micromorphology changes of the joint surface. Among them, the parameters such as root mean square height (Sq), arithmetic mean height (Sa), reverse load area ratio (Smc), and minimum autocorrelation length (Sal) can better characterize the joint surface deterioration of rock samples under the action of fracture water pressure. The test results have a certain reference value for studying the fault response under the action of reservoir water.